Increased cytotoxicity of 3,5 dihydroxy -7- methoxyflavone in MIA PaCa-2 and Panc28 pancreatic cancer cells when used in conjunction with proliferative compound 3,5 dihydroxy-7-methoxyflavanone both derived from Chromolaena leivensis (Hieron) (2016)
Over 5000 flavonoids have been identified so far and many of these are known to have antineoplastic properties. The relationships between the targeting activities by these compounds on cancer cells and the specific features that determine their molecular structures are not completely elucidated. Here we report the differential cytotoxic effects of two unsubstituted ring B flavonoids that differ solely in the presence of a C2, C3 double bond in ring C, on human cancer cells of the lung (A549), pancreas (MIA PaCa-2, Panc28), colon (HCT 116, CaCo-2), Liver (HepG2), and breast (SKBr3). These compounds were extracted from Chromolaena leivensis (Hieron) a plant belonging to the genus Chromolaena reputed to have antitumor activities. 3, 5 dihydroxy-7-methoxyflavone induce apoptosis in cancer cells of the lung A549, pancreas MIA PaCa-2 and Panc28, and colon HCT116, but not on Caco-2; whereas 3,5 dihydroxy-7-methoxyflavanone display proliferative effects in A549, Panc 28, MIA PaCa, and HCT116 cells at low concentrations, and slight cytotoxicity only on CaCo-2, a cancer cell line with a higher differentiation status than other cells tested. At the concentrations studied (5-80µM) neither compound demonstrated activity against cancer cells of the liver (HepG2) or breast (SKBr3) as indicated by MTT cell viability assays. When used in combination with 3,5 dihydroxy-7-methoxyflavone in pancreatic cancer cells, the targeting preference of 3, 5 dihydroxy-7-methoxyflavanone is altered, and a significant increase in inhibition of cell viability is observed 48 hours after dosing. The presence or absence of the C2, C3 double bond in ring C, accounts for electrochemical and structural changes that dictate differential specificity towards cancer cells. 3,5 dihydroxy-7-methoxyflavone has a more planar structure, whereas the absence of the double bond in C2, C3 causes ring B to adopt a perpendicular orientation to the plane formed by rings A and C and the OH group at C3.